MKTG 14 Principles of Marketing - Lamb, Charles W.; Hair, Joseph F.; McDaniel, Carl (Cengage, 2025)
MKTG, 14th Edition, demonstrates the practical application of marketing principles in real-world scenarios. Relevant and timely examples help students better understand and apply marketing principles. A user-friendly design makes it easy to navigate and comprehend key concepts. By connecting theory to real-life situations, Lamb/Hair/McDaniel's MKTG, 14th Edition, bridges the gap between classroom learning and the modern marketing industry -- helping students recognize the practicality of marketing and develop essential skills for success.